Pengaruh Capital Intensity, Kepemilikan Institusional dan Ukuran Perusahaan terhadap Agresivitas Pajak - Sri Lestari Yuli Prastyatini; May Yesti Trivita (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
Tax aggressiveness is tax planning that occurs due to differences in interests between countries where taxes are the main source of income for the interests and prosperity of the country. Still, taxes are a burden for companies that can reduce company profits. This study was conducted to test the effect of Capital Intensity (CI), Institutional Ownership (KI), and Firm Size (UK) on Tax Aggressiveness. The data used are secondary data derived from the financial statements and annual reports of mining companies listed on the Indonesia Stock Exchange. The population in this study are mining sector companies listed on the Indonesia Stock Exchange from 2016 to 2020. The sampling technique used is a purposive sampling technique with a year of observation for 5 years. The data analysis method used in this research is multiple linear regression analysis. Data were analyzed using IMB SPSS version 25. The results showed that capital intensity did not positively affect tax aggressiveness, and institutional ownership did not negatively affect tax aggressiveness. In contrast, the company's size positively affects tax aggressiveness. Keywords: Tax Aggressiveness, Capital Intensity, Institutional Ownership, Firm Size